Selective hydrodefluorination of hexafluoropropene to industrially relevant hydrofluoroolefins - Phillips,N; White,A; Crimmin,M (Advanced Synthesis & Catalysis, 2019)
The selective hydrodefluorination of hexafluoropropene to HFO1234ze and HFO1234yf can be achieved by reaction with simple group 13 hydrides of the form EH3 ⋅ L (E=B, Al; L=SMe2, NMe3). The chemoselectivity varies depending on the nature of the group 13 element. A combination of experiments and DFT calculations show that competitive nucleophilic vinylic substitution and additionelimination mechanisms involving hydroborated intermediates lead to complementary selectivities.